2019
DOI: 10.1186/s12881-019-0806-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel EYA4 variant in Slovak family with late onset autosomal dominant hearing loss: a case report

Abstract: Background Progressive bilateral sensorineural deafness in postlingual period may be linked to many different etiologies including genetic factors. Identification of the exact deafness cause may, therefore, be quite challenging. Here we present a family with late-onset hearing loss as an autosomal dominant trait caused by a novel EYA4 mutation. Case presentation Forty-four years old female proband clinically investigated for progressive hearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The most commonly reported hearing loss is mild to moderate mid-frequency hearing loss at onset, which is called "Cookie-bite" audiogram. Subsequent hearing loss also affects high frequencies, resulting in moderate to severely at or downward-sloping audiograms [11]. The proband in this study showed mild-to-moderate hearing loss with medium-and high-frequency descending hearing loss.…”
Section: Discussionmentioning
confidence: 53%
“…The most commonly reported hearing loss is mild to moderate mid-frequency hearing loss at onset, which is called "Cookie-bite" audiogram. Subsequent hearing loss also affects high frequencies, resulting in moderate to severely at or downward-sloping audiograms [11]. The proband in this study showed mild-to-moderate hearing loss with medium-and high-frequency descending hearing loss.…”
Section: Discussionmentioning
confidence: 53%
“…Our results indicated that the region of amino acids 124 to 343 may not play a key role in the maintenance of normal cardiac gene regulation and may not be the pathogenic region causing dilated cardiomyopathy, because the genotype–phenotype correlation of EYA4 mutations has been previously suggested to contribute to hearing loss and associated dilated cardiomyopathy (8,10). Furthermore, analyzed from the nonsense or deletion mutations in EYA4 gene including our result (1,8,10,19,23,25–31), it is suggested that the theory of genotype–phenotype correlation of EYA4 mutations about the prevalence of dilated cardiomyopathy should be rejected because of the non-correspondence of deleted amino acid region with the prevalence of dilated cardiomyopathy (Fig. 6).…”
Section: Discussionmentioning
confidence: 70%
“…Depending on the objectives of the study, different experimental settings and laboratory protocols can be used. To give an overview of the potential applications of the pDESTsplice and pSpliceExpress vectors, we have compiled 25 published studies [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ], in which these minigene systems were used ( Table 1 and Table 2 ). In most of the works, the usage of pSpliceExpress has been described ( n = 18).…”
Section: Studies Using the Pdestsplice And Pspliceexpress Vectorsmentioning
confidence: 99%
“…In most of these studies, the assumed Expression clone was sequenced ( n = 10) or a combination of sequencing and control cleavage with restriction enzymes was performed ( n = 7). Varga et al checked their Expression clones by colony PCR in addition to sequencing [ 56 ].…”
Section: Studies Using the Pdestsplice And Pspliceexpress Vectorsmentioning
confidence: 99%